Optimizing Connectivity and Network Management with SDN Technology on VANET Using the SSF Method - Dinata, Hane Yorda; Suranegara, Galura Muhammad (Aviation Electronics, Information Technology, Telecommunications, Electricals, and Controls (AVITEC), 2025)
Vehicular Ad-Hoc Networks (VANET) represent a crucial innovation in transportation technology, enabling vehicle-to-vehicle (V2V) and vehicle-to-infrastructure (V2I) communication. However, VANET faces challenges such as signal fluctuations, data security issues, and high mobility, which affect network reliability. This study aims to optimize connectivity and network management in VANET using the Strongest-Signal-First (SSF) method supported by Software-Defined Networking (SDN). The research was conducted through simulations using Mininet-WiFi. The system was designed with two vehicles and four access points to evaluate the performance of the SSF method, focusing on quality of service (QoS) parameters such as data transfer, jitter, packet loss, and bandwidth. Data were collected over a 30-second simulation under varying bandwidth conditions. The results demonstrate that the SSF method effectively maintains communication reliability, achieving a maximum packet loss of only 0.05% and an average data transfer rate of 285 – 324 kB. However, the effects of fading and network dynamics caused fluctuations in minimum transfer rates (102 – 114 kB) and jitter (0.1 – 1.0 ms), particularly at lower bandwidths. The SSF method has proven to enhance communication stability in VANET. Nevertheless, challenges such as fading and high mobility require additional mechanisms to further improve network performance in dynamic environments.